Direct determination of Al, As, Cu, Fe, Mn, and Ni in fuel ethanol by simultaneous GFAAS using integrated platforms pretreated with W-Rh permanent modifier together with Pd+Mg modifier - De Oliveira, Adriana Paiva [UNESP]; De Moraes, Mercedes [UNESP]; Gomes Neto, José Anchieta [UNESP]; Lima, Eder Cláudio (My University, 2002)
A method is proposed for the simultaneous determination of Al, As, Cu, Fe, Mn, and Ni in fuel ethanol by electrothermal atomic absorption spectrometry (ETAAS) using W-Rh permanent modifier together with Pd(NO3)2 + Mg(NO3)2 conventional modifier. The integrated platform of a transversely heated graphite atomizer (THGA) was treated with tungsten, followed by rhodium, forming a deposit containing 250 μg W + 200 μg Rh. A 500-μL volume of fuel ethanol was diluted with 500 μL of 0.14 mol L-1 HNO3 in an autosampler cup of the spectrometer. Then, 20 μL of the diluted ethanol was introduced into the pretreated graphite platform followed by the introduction of 5 μg Pd(NO3)2+ 3 μg Mg(NO3)2. The injection of this modifier was required to improve arsenic and iron recoveries in fuel ethanol. Calibrations were carried out using multi-element reference solutions prepared in diluted ethanol (1+1, v/v) acidified to 0.14 mol L-1 HNO3. The pyrolysis and atomization temperatures of the heating program were 1200°C and 2200°C, respectively, which were obtained with multielement reference solutions in acidic diluted ethanol (1+1, v/v; 0.14 mol L-1 HNO3). The characteristic masses for the simultaneous determination in ethanol fuel were 78 pg Al, 33 pg As, 10 pg Cu, 14 pg Fe, 7 pg Mn, and 24 pg Ni. The lifetime of the pretreated tube was about 700 firings. The detection limits (D.L.) were 1.9 μg L-1 Al, 2.9 μg L-1 As, 0.57 μg L-1 Cu, 1.3 μg L-1 Fe, 0.40 μg L-1 Mn, and 1.3 μg L-1 Ni. The relative standard deviations (n = 12) were 4%, 4%, 3%, 1.5%, 1.2%, and 2.2% for Al, As, Cu, Fe, Mn, and Ni, respectively. The recoveries of Al, As, Cu, Fe, Mn, and Ni added to the fuel ethanol samples varied from 81% to 95%, 80% to 98%, 97% to 109%, 85% to 107%, 98% to 106% and 97% to 103%, respectively. Accuracy was checked for the Al, As, Cu, Fe, Mn, and Ni determination in 10 samples purchased at a local gas station in Araraquara-SP City, Brazil. A paired t-test showed that at the 95% confidence level the results were in agreement with those obtained by single-element ETAAS.